PENERAPAN SISTEM MANAJEMEN PENDIDIKAN BERBASIS TOTAL QUALITY MANAGEMENT (TQM) DI LEMBAGA PENDIDIKAN - Hadijaya, Yusuf; Fahada, Nazli; Iman, Mujhirul; Irwansyah, Irwansyah; Nasution, Rizki Hasanah (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
This article discusses total quality management in its implementation in educational institutions. Education plays a crucial role in shaping a competitive society. One of the latest emerging approaches to improving the quality of education is Total Quality Management (TQM). Total Quality Management is one of the models or methods used to improve the quality of education in educational institutions. Total Quality Management is one of the keys to the success of the most effective educational goals. Because TQM prioritizes the integration of all functions and processes and empowers and involves all elements in the education system. TQM must be applied continuously and continuously in order to achieve educational goals, which provide satisfaction to students, parents and the community